THE LINGUISTIC MANIFESTATIONS OF GENDERLECT IN“EMILY IN PARIS” TV SERIES: - Harutyunyan, Kristine; Sargsyan, Anna (Armenian Folia Anglistika, 2024)
Sociolinguists study genderlect to better understand how gender and language intersect and to challenge stereotypes and assumptions about gendered communication. Genderlect refers to the idea that men and women, on average, tend to have distinct communication styles and tendencies. The aim of the present article is to study the genderlect in one of the most famous TV series from the sociolinguistic point of view. Within the frames of the article we attempt to illustrate the linguistic differences between men and women, to highlight various conversational behaviors and to detect the reasons of this gender-based diversity. The factual data of the research was taken from the scripts of the TV series, conditioned by the fact that the gendered language is best illustrated in everyday speech. The main findings of the article are the manifestation and clarification of linguistic differences of genderlect in the TV series.